1986
DOI: 10.1016/0165-1218(86)90036-4
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of para-substituted α-methylstyrene oxide derivatives with Salmonella

Abstract: A series of 5 para-substituted alpha-methylstyrene oxide derivatives have been synthesized and together with alpha-methylstyrene oxide as well as styrene oxide have been studied as to their mutagenicity with the TA100 and TA1535 strains of Salmonella typhimurium. A multiple regression analysis model has been developed which describes the mutagenicity of the alpha-methylstyrene oxides in TA100. An increase in van der Waals volume was the most important variable in the model with greater improvement occurring wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The stereochemistry of urinary metabolites from cumene-treated rabbits suggested that S-(ϩ)-2-phenylpropionic acid was not from oxidation of R-(ϩ)-2-phenyl-1-propanol (Ishida and Matsumoto, 1992). Rapid rearrangement of AMS oxide to phenylpropionaldehyde was observed in this and other studies (Rosman et al, 1986); therefore, formation of M16 from this pathway is highly feasible. However, R-(Ϫ)-2-phenylpropionic acid has been shown to partially isomerize to its S-(ϩ)-isomer in rats (Yamaguchi and Nakamura, 1985); therefore, formation of M16 from oxidation of M14 cannot be FIG.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The stereochemistry of urinary metabolites from cumene-treated rabbits suggested that S-(ϩ)-2-phenylpropionic acid was not from oxidation of R-(ϩ)-2-phenyl-1-propanol (Ishida and Matsumoto, 1992). Rapid rearrangement of AMS oxide to phenylpropionaldehyde was observed in this and other studies (Rosman et al, 1986); therefore, formation of M16 from this pathway is highly feasible. However, R-(Ϫ)-2-phenylpropionic acid has been shown to partially isomerize to its S-(ϩ)-isomer in rats (Yamaguchi and Nakamura, 1985); therefore, formation of M16 from oxidation of M14 cannot be FIG.…”
Section: Discussionmentioning
confidence: 67%
“…AMS oxide is mutagenic in Salmonella assays (Rosman et al, 1986) and reacts with GSH, forming a mercapturic acid conjugate (M12) excreted in urine. Therefore, AMS oxide might play a role in the higher incidence of alveolar/bronchiolar adenoma and carcinoma observed in the lung of cumene-treated mice in the National Toxicology Program toxicity studies.…”
Section: Disposition and Metabolism Of Cumene In Micementioning
confidence: 99%
“…An alternative theory is that DNA damage could contribute to lung cancer (Hong et al 2008), suggesting that the results of these rodent studies could be relevant to humans. With respect to the alternative theory, it should be noted that cumene was not mutagenic in studies conducted by the NTP (2009), but one of its metabolites (a-methylstyrene oxide) has been shown to be mutagenic in vitro (Rosman et al 1986). However, the separate observation that a-methylstyrene, a direct precursor to a-methylstyrene oxide, did not induce the mouse lung and rat nasal tumors that are associated with cumene (NTP 2007) seems more compatible with the hypothesis that cumene acts via a non-genotoxic mode of action.…”
Section: Carcinogenicitymentioning
confidence: 99%
“…α-Methylstyrene α-Methylstyrene is a metabolite of isopropyl benzene that has been found in the exhaled air of mice after oral administration, but was practically absent in that of rats (see Section 3.2). As α-methylstyrene can be converted to α-methylstyrene oxide, which is genotoxic in Salmonella mutagenicity tests, it is suspected that αmethylstyrene plays a role in the induction of isopropyl benzene-induced lung tumours in mice (Chen et al 2011;Rosman et al 1986). After inhalation exposure of mice and rats to α-methylstyrene, effects similar to those that occur after inhalation of isopropyl benzene are observed, for example hyperplasia of the olfactory epithelium.…”
Section: Relevance Of the Nasal Tumours For Humansmentioning
confidence: 99%